Pengaruh Peran dan Motivasi Penyuluh Pertanian Terhadap Inovasi Teknologi Budidaya Tanaman Padi Sawah di Kecamatan Kupang Timur, Kabupaten Kupang Provinsi Nusa Tenggara Timur - Wely Yitro Pello; Musa Frengkianus Banunaek; Emi Renoat (Jurnal Penyuluhan, 2019)
This research aimed to find out rice plant technology innovation level in East Kupang Sub District, to find out the effect of extension agent’s role and job motivation on rice plant technology innovation, and to find out the simultaneous effect of extension agent’s role and motivation on rice plant technology innovation. Data analysis was conducted using multiple regression analysis. The result of research found that Rice Plant Cultivation Technology Innovation (Y) in East Kupang Sub District belonged to medium category (78.33%); it is indicated with the aspect of rice plant cultivation technology innovation dissemination by extension agent of 74.50% only and the aspect of farmers’ participation in wet-rice cultivation technology of 66.17%. The agricultural extension agent’s role factor belonged to high category (50.00%), while agricultural extension agent’s motivation factor belonged to medium category (60.00%). Agricultural Extension Agent factor affected significantly the rice cultivation technology innovation (Y), as indicated with three aspects: extension agent’s role as educator and facilitator, role as analyzer and planner, and role as evaluation expert of activity and education result. Agricultural extension agent’s motivation factor significantly affected the rice cultivation technology innovation (Y), as indicated with three aspects: extension agent’s motivation on basic need, status/social need, and work performance need. Extension agent’s role and motivation simultaneously affected rice plant technology innovation with Fstatistic value of 13.11.